If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -2x = 4x + -3 Reorder the terms: 15 + -2x = -3 + 4x Solving 15 + -2x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + -2x + -4x = -3 + 4x + -4x Combine like terms: -2x + -4x = -6x 15 + -6x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -6x = -3 + 0 15 + -6x = -3 Add '-15' to each side of the equation. 15 + -15 + -6x = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -6x = -3 + -15 -6x = -3 + -15 Combine like terms: -3 + -15 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| K*2+4=6 | | 8x-14=9x+6 | | 29.50=1.50x+7 | | 2*(x+1)=6 | | x^2(x^2-7x-18)=0 | | 20(X+8)=40X | | 2(X+8)=40X | | 6(-2-3)=6 | | X^2-4x-1152=0 | | 2(750-x)+3x=1750 | | (3x+11)-2x=19 | | 7(5-x)-3(-4-6x)=-8 | | w^2+0.11w=0.057 | | 3=-3x+29 | | 0.5x/x | | -4(5x-2)=4(2x-3) | | x=9x+40 | | -6d-3d+3=-12 | | 20x^3-40x=0 | | 7x-21y=-14 | | 6l+4m-5l-4m-l+m= | | 3(4x-7)=-2(3x-5) | | 3X-4(X-2)=7+5(X+5) | | 3a=6(a-3) | | 5/3x18 | | 2(3x+8)=5(x+2) | | 20x^2-x-4=0 | | 15n^3+20n^2= | | 9x-2=x+6 | | x*55=-220 | | 27x^2+36x-6x-8= | | x/2=7/11 |